KEDUDUKAN FILSAFAT HUKUM DALAM PEMBENTUKAN POLITIK HUKUM NEGARA INDONESIA UNTUK MEWUJUDKAN NEGARA KESEJAHTERAAN (Welfare State) - Sumartini, Siti; Alam, Kodrat (Universitas Wiralodra, 2019)
The legal philosophy and legal politics of a country in the perspective of academic studies are two (2) highly correlated and influential things. The law is basically not sterile from its social subsystem. Politics often intervenes on the actions and execution of the law so that the question arises about which subsystem between law and politics is more supremetive. This question arises because of the abundance of blunt laws in the interruption arbitrariness of authority, the law is incapable of upholding justice and cannot present itself as a matter that should be the legal task of solving it. The linkage between philosophy and law that only philosophical approach to law is an attempt to provide rational thought about time-bound law, or attempt to formulate a general theory of the legal order to meet some of the needs of legal development or state development. With the philosophy of law philosophers on the formation of a country's legal politics, it will manifest a paradigm of the welfare state. Keyword: Philosophy of law, status and legal policy